The short-term associations of particular matters on non-accidental mortality and causes of death in Chiang Mai, Thailand: a time series analysis study between 2016-2018 - Chaicharn Pothirat (2020)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. Open burnings, agricultural and forest fires, are the major sources of particulate matters (PM) in Chiang Mai during dry season. We aim to determine the association of an increased daily PM (PM10, PM2.5) and daily non-accidental mortality and causes of death in Chiang Mai. The association between PM and daily non-accidental mortality including causes of death were analyzed using a generalized linear model with Poisson distribution. The results showed that PM10 and PM2.5 were associated with daily non-accidental mortality on different lag days (adjusted RR range from 1.009–1.018 and 1.016 for each 10 µg/m3 increment of PM10 and PM2.5, respectively). The causes of death associated with PM10, PM2.5 found on different lag days were chronic obstructive pulmonary disease (COPD), coronary artery disease (CAD), and sepsis. We concluded that PM10 and PM2.5 are associated with daily non-accidental mortality and causes of death were COPD, CAD, and sepsis.